2010
DOI: 10.1007/s11999-009-1206-y
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Properties Remain Altered in a Chronic Rat Rotator Cuff Model

Abstract: Background Chronic rotator cuff tears are often associated with pain or poor function. In a rat with only a detached supraspinatus tendon, the tendon heals spontaneously which is inconsistent with how tears are believed to heal in humans. Questions/purposes We therefore asked whether a combined supraspinatus and infraspinatus detachment in the rat would fail to heal and result in a chronic injury in the supraspinatus tendon. Methods We acutely detached the supraspinatus and infraspinatus tendons in a rat model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
2
28
0
6
Order By: Relevance
“…Photomicrographs were blindly graded by 3 observers for assessment of cellularity and cell shape based on a scale of 0 (normal), 1 (mild changes), 2 (moderate changes), and 3 (marked changes), as done previously. 7 The same images were also analyzed for collagen organization with quantitative polarized light microscopy. With use of this technique, angular deviation (a measure of disorganization) was calculated for each specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Photomicrographs were blindly graded by 3 observers for assessment of cellularity and cell shape based on a scale of 0 (normal), 1 (mild changes), 2 (moderate changes), and 3 (marked changes), as done previously. 7 The same images were also analyzed for collagen organization with quantitative polarized light microscopy. With use of this technique, angular deviation (a measure of disorganization) was calculated for each specimen.…”
Section: Methodsmentioning
confidence: 99%
“…When making decisions about repair options, clinicians often refer to animal studies of rotator cuff injury that include mice (Thomopoulos et al, 2007), rats (Soslowsky et al, 1996), sheep (Gerber et al, 1999), rabbits (Björkenheim, 1989), dogs (Kujat, 1990), goats and others (Adams et al, 2006;Das et al, 2011;Grumet et al, 2009;MacGillivray et al, 2006;Peltz et al, 2009;Uggen et al, 2010). Although a variety of animal models have been used to study rotator cuff disease, questions remain about their relevance to humans, because of differences in their basic muscle architecture, bony anatomy and healing capacity (Brand, 2008;Dourte et al, 2010;Soslowsky et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that tendon cross-sectional area remained constant in the G-CSFtreated group between 12 and 19 days, whereas the control group exhibited a decrease in cross-sectional area. Dourte et al have previously shown that normally healing tendons demonstrate a steady decrease in cross-sectional area during remodeling [9]. The lack of significant increases in mechanical properties and decreases in tendon cross-sectional areas may represent delayed healing.…”
Section: Discussionmentioning
confidence: 99%